PENGARUH ENVIRONMENTAL, SOCIAL, & GOVERNANCE (ESG) DISCLOSURE SERTA KINERJA KREDIT TERHADAP PROFITABILITAS BANK - Cahyani, Anindia Putri; Moh. Athoillah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The study aims to analyze the impact of Environmental, Social, & Governance (ESG) disclosure, as well as Loan to Deposit Ratio (LDR) and Net Interest Margin (NIM) on the Return on Assets (ROA) of 10 banks that have sustainability reports and have ESG index scores in 2018-2021. The research method used in this research is a quantitative research method with a panel data regression analysis technique. The research data used is secondary data with a purposive sampling technique. The results of this study show that social variables, governance variables and NIM have a significant impact on ROA. The findings in this study have practical implications for corporate stakeholders in evaluating policies to disclose ESG performance.